Stratigraphic Studies of the Snow Cover in Mizuho Plateau - Watanabe, O. (1978)
P(論文) This paper is concerned with the stratigraphic investigations conducted by means of pits and snow cores on the snow cover of Mizuho Plateau in 1970-1971 and 1974-1975. The snow cover is basically composed of the unit layer (minimum structural units) and the layer boundaries caused by hiatus phenomena. The natures of these two stratigraphic elements are revealed through the studies of structural and physical properties, as well as oxygen isotope ratios. In the high accumulation region lower than 1700-2000m a. s. l., the characteristics of the unit layer corresponded well to the seasonal changes of climatic conditions. In the inland region of less accumulation, the hiatus frequently occurs in the formation of the annual layer and almost all of the stratigraphic elements are strongly deformed by metamorphic processes. Determination of the annual accumulation rate was investigated by means of the stratigraphic interpretation, seasonal variation of oxygen isotope ratios and detection of the reference horizons by vertical profiles of gross β activity. The oxygen isotope method is not so effective in the estimation of the annual accumulation rate in areas other than high accumulation region. Accumulation shows a regional distribution such as 60cm snow per year in the coastal region and 15cm snow per year at 3400m a. s. l. According to the regional variation of snow stratification, the snow cover in Mizuho Plateau is divided characteristically into three regions with elevation boundaries lying in 1900-2100m and 2800-3200m a. s. l. departmental bulletin paper